Efficacy of P188 on lapine meniscus preservation following blunt trauma. (July 2015) - Coatney, Garrett A; Abraham, Adam C.; Fischenich, Kristine M.; Button, Keith D.; Haut, Roger C.; Haut Donahue, Tammy L.
Abstract: Traumatic injury to the knee leads to the development of post-traumatic osteoarthritis. The objective of this study was to characterize the effects of a single intra-articular injection of a non-ionic surfactant, Poloxamer 188 (P188), in preservation of meniscal tissue following trauma through maintenance of meniscal glycosaminoglycan (GAG) content and mechanical properties. Flemish Giant rabbits were subjected to a closed knee joint, traumatic compressive impact with the joint constrained to prevent anterior tibial translation. The contralateral limb served as an un-impacted control. Six animals (treated) received an injection of P188 in phosphate buffered saline (PBS) post trauma, and another six animals (sham) received a single injection of PBS to the impacted limb. Histological analyses for GAG was determined 6 weeks post trauma, and functional outcomes were assessed using stress relaxation micro-indentation. The impacted limbs of the sham group demonstrated a significant decrease in meniscal GAG coverage compared to non-impacted limbs ( p <0.05). GAG coverage of the impacted P188 treated limbs was not significantly different than contralateral non-impacted limbs in all regions except the medial anterior ( p <0.05). No significant changes were documented in mechanics for either the sham or treated groups compared to their respective control limbs. This suggests that a single intra-articular injection of P188 shows promise in prevention of trauma induced GAG loss.